Evaluation of Erectile Functions in Patients with Early and Delayed Penile Fracture Repair Using of International Index of Erectile Function-5 - Naqib Ullah, Zakir Khan, Navid Khan, Fahim Ullah, Muhammad Izhar, Sajid Shakeel (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Penile fracture is a rare but serious urological emergency that is associated with erectile dysfunction if not treated promptly. Early repair is traditionally advocated but conflicting evidence on delayed repair outcomes requires further evaluation using standardized measures such as IIEF 5. Methodology: A prospective observational study was carried out for a 12-month period in 100 male patients aged 18 years of age or older with penile fracture and normal baseline erectile function. Fifty patients each were divided into two groups, early repair (≤24 hours) and delayed repair (>24 hours). Injuries were recorded as well as demographic data, injury specifics and intraoperative findings. Erectile function was the primary outcome measured with the IIEF 5 at baseline, 1, 3 and 6 months postoperatively. Complication rates, penile curvature and overall patient satisfaction were secondary outcomes. SPSS version 26 was used for statistical analysis with t tests, Mann Whitney U tests, and chi square tests as well as logistic regression. Results: In a study of 100 patients with penile fractures, and 50 patients underwent early repair (≤ 24 hours) and 50 patients underwent delayed repair (> 24 hours). Between the 2 groups, baseline demographics and injury mechanisms were similar. IIEF 5 scores decreased by a temporary amount at one month postoperatively in both groups, but improved in a stable manner. There was no statistically significant difference in erectile function between groups by 3 and 6 months. Furthermore, patients undergoing delayed repair when indicated had similar overall complication rates, incidence of penile curvature, and patient satisfaction as patients undergoing early repair. Conclusion: Long term erectile function was comparable to both early and delayed repair. There were no differences between the groups in IIEF 5 scores, complication rates or patient satisfaction. Therefore, delayed repair is a possible option when early intervention is not possible. Keywords: Penile Fracture; Erectile Dysfunction; IIEF‑5; Early Repair; Delayed Repair